A cross-sectional survey of poultry management systems, practices and antimicrobial use in relation to disease outbreak in Pakistan - Farrukh Saleem; Aqsa Ameer; Farhan Afzal; Muhammad Usman; Hamid Irshad; Sadia Sattar; Umer Zeeshan Ijaz; Sundus Javed (BMC Research Notes)
Abstract Objectives The study aimed to examine how management practices, farming setup and breed influence disease outbreaks. It also sought to investigate the frequency and types of antimicrobials used, as well as the relationship between antimicrobial usage and disease occurrences. Methods We conducted a survey of 140 poultry farms [Broiler farms = 66; Layer farms = 36; Local (Desi and its crosses) farms = 38] across major poultry producing regions of Pakistan. The gathered information covered demographics as well as the farming associated parameters including size, type of the farms, management practices, breeds raised, disease outbreak and antimicrobials use. Results Using contingency analyses and log binomial regression models, we identified Broiler control sheds at high risk of disease. Diseases such as Avian Influenza, Newcastle Disease, and Fowl Typhoid were frequently reported and their outbreaks were associated with low cleaning frequency, high stocking density, bedding material using rice husk, and canola as a major feed ingredient. Farmer education was associated with a decrease in disease outbreak. Antimicrobial use was associated with farming experience, farm size, type and breed. Conclusion High disease incidence is associated with management practices and breed types across various farm setups. Experienced Broiler farmers often report disease outbreaks and use antimicrobials more frequently. Educated farmers, however, experience fewer outbreaks and can better regulate antimicrobial usage.